Prevention, Diagnosis, and Treatment of Lung Cancer - Adonis, Marta (IntechOpen, 2017)
Lung cancer is the number one cause of cancer deaths around the world. This devastating disease takes strength not only in people who smoke but also in poor people that eat polluted food and use heating sources, and in those exposed naturally to toxic compounds present in indoor and outdoor environments. Lung cancer patients and their families wait actions from the science that give not only answer to their demands but also a light of hope at the moment of receiveing the diagnosis. This book meets the experience of several researchers who dedicate many hours a day to find not only the cure of lung cancer but also the way to convert the pathology of this chronic disease. In 12 chapters, the lectures will give information related to the relationship of lung cancer and smoking habit, the crucial role of the image technology for diagnosis of lung cancer, and a molecular vision of prevention, diagnosis, and treatment of lung cancer. The authors with a clinic and/or lab vision and with a great spirit to collaborate with the science and with each past, present, and future patient and their families have dedicated many hours to write each chapter. Probably, the final answer to find the cure of lung cancer is not in this book. However, the lectures will give scientific information that will contribute in the near future improvement to the life quality of the patients.